Towards a robust interpretation of forensic analysis of phosphorus and calcium traces in gunshot residue. Issue 10 (14th August 2019) - Brożek-Mucha, Zuzanna; Nunziata, Felice; Ross, Peter; Mucha, Dariusz
Abstract : The source identification of calcium and phosphorus traces in gunshot residue can be obtained using SEM-EDX for forensic purposes. Abstract : Standard analysis of inorganic gunshot residue aims nowadays at lead, antimony and barium particles of spherical shape, although other elements are detected that may be indicative of the ammunition brand or interaction with specific materials. Calcium and phosphorus can be present in the particle systems examined. There are two main sources of these elements in gunshot residue: components of the ammunition, e.g. Eley brand .22 long rifle caliber and bone fragments created during contact and close-range shooting. Samples of human bones of various ages and the residue from the interior of spent cartridges of ten different products of Eley brand .22 long rifle caliber ammunition were systematically characterised as reference materials to aid the interpretation of candidate GSR particles detected in evidence samples. We found that Ca : P ratios obtained by means of scanning electron microscopy with energy dispersive X-ray spectrometry from GSR particles larger than about 10 micrometres characterised bone fragments reliably. Although Ca and P may be detected as traces, for smaller (micron and sub-micron) particles the Ca : P ratio is not a reliable indicator of bone material. But in such cases qualitative interpretation taking into account interdisciplinary information can be achieved for forensic purposes. Three case studies encompassing various types and amounts of gunshot residue identified the possibilities and limitations in the differentiation between the potential sources of calcium and phosphorus present in inorganic gunshot residue.